Identifikasi Preferensi Konsumen Terhadap Minat Beli Kerupuk Rambak Produk Teaching Factory Cerva Politeknik Negeri Banyuwangi - Wicaksono, Dani Agung; Firdaus, Hakiki; Wilujeng, Ninik Sri Rahayu; Ton, Sefri; Sari , Dewiarum (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study was conducted to analyze consumer preferences and purchase intentions regarding krauz rambak crackers, a product developed by the Teaching Factory Cerva of the Livestock Product Processing Technology Department at Banyuwangi State Polytechnic. These crackers are made from processed cowhide and are available in three flavor variants original, balado, and grilled corn. Employing a quantitative descriptive approach, the research involved 354 active students selected through purposive sampling. Data were collected via observation, questionnaire distribution, and interviews, and analyzed using a Likert scale with the assistance of Microsoft Excel 2019. The results indicated that taste and price received positive evaluations from consumers, with an average score of 4.16 (liked). The original flavor was the most preferred variant 4.26, while grilled corn ranked lowest 4.00. The product’s price was considered highly affordable, receiving the highest score of 4.28. On the other hand, consumer purchase intention fell under the “moderate interest” category, with an average score of 3.36. While consumers expressed willingness to buy and recommend the product, further efforts are needed to improve product information dissemination. Krauz rambak crackers have promising market potential among students, especially if promotional strategies and flavor development are optimized.